Pengaruh Likuiditas dan Solvabilitas terhadap Profitabilitas pada PT Indofood CBP Sukses Makmur Tbk Periode 2014-2023 - Widiawati, Aisah; Budi, Saksono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Profitability is a crucial indicator of a company’s financial performance and long-term sustainability. This study was conducted to determine the effect of liquidity and solvency on the profitability of PT Indofood CBP Sukses Makmur Tbk for the period 2014–2023. The research was motivated by the importance of understanding how internal financial ratios specifically the Current Ratio (CR) and Debt to Equity Ratio (DER) influence the company’s ability to generate profit, measured by Return on Assets (ROA). A quantitative approach was applied using an associative method to examine the relationship between the variables. The data used were secondary data, sourced from the company's financial reports accessed via the official websites of the Indonesia Stock Exchange and the company itself. A total of 10 data samples were selected using purposive sampling. Data analysis was performed using multiple linear regression with SPSS version 27. Prior to regression analysis, classical assumption tests were conducted, including tests for normality, heteroscedasticity, multicollinearity, and autocorrelation. The results revealed that CR has a significant partial effect on ROA, while DER does not show a significant individual effect. However, both variables simultaneously have a significant impact on profitability. The findings suggest the importance of managing liquidity and capital structure to improve financial performance.